2022
DOI: 10.2147/prbm.s383743
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Psychological Capital, Coping Style and Emotional Intelligence with Self-Rated Health Status of College Students in China During COVID-19 Pandemic

Abstract: Background COVID-19 lockdown can lead to mental health problem, and the problem is heterogeneous across individuals. In this study, we aimed to explore the association between the self-reported health status, emotional coping style, emotional intelligence and positive psychological state of college students during the COVID-19 pandemic in China. Methods The questionnaires of Self-rated Health Measurement Scale (SRHMS), Emotional Intelligence Scale (EIS), Psychological C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In other words, a positive mentality elevates people’s ability of thinking and motivates them to proactively eliminate the stressor. Jing et al ( 2022 ) pointed out that psychological capital provides people with the energy they need to confront stressors, and the success in resolving difficult situations will generate confidence and psychological satisfaction which protect people from emotional distress and mental disorders. The finding was supported by several studies (Jalil et al, 2021 ; Wu et al, 2020 ); however, most studies were conducted on college students or other adult population.…”
Section: Emotional Intelligence and Anxietymentioning
confidence: 99%
“…In other words, a positive mentality elevates people’s ability of thinking and motivates them to proactively eliminate the stressor. Jing et al ( 2022 ) pointed out that psychological capital provides people with the energy they need to confront stressors, and the success in resolving difficult situations will generate confidence and psychological satisfaction which protect people from emotional distress and mental disorders. The finding was supported by several studies (Jalil et al, 2021 ; Wu et al, 2020 ); however, most studies were conducted on college students or other adult population.…”
Section: Emotional Intelligence and Anxietymentioning
confidence: 99%
“…[11][12][13] College students mental health issues are particularly severe due to their changing living conditions and mounting academic pressure, and they are becoming a major global public health concern. [14,15] A study found that among American college students, the incidence rate of depression (DEP) was 17.3%, the incidence rate of panic disorder was 4.1%, the incidence rate of anxiety (ANX) disorder was 7.0%, and the suicide thought accounted for 6.3%. [16] The psychological health problems of Russian college students, such as ANX and DEP, are also particularly serious.…”
Section: Introductionmentioning
confidence: 99%
“… 14 It also equips the students to meet present-day academic challenges and competitions and good health status. 24 , 25 Thus, Trait EI can be an important facilitator for college students in building the capacity to deal with the various stressors of life. Therefore, understanding the association between personality factors and Trait EI can be significant.…”
Section: Introductionmentioning
confidence: 99%